Manufacturing strategy incorporated in aggregate production planning through a multi-objective linear programming model - Almeida Filho, Adiel Teixeira de; De Souza, Fernando Menezes Campello; De Almeida, Adiel Teixeira (Brazilian Journal of Operations & Production Management, 2010)
Aggregate Planning activity is a relevant stage of the production planning process and has been regularly discussed in the literature for almost 50 years. It seeks to suggest a production strategy in order to meet demand, given capacity constraints. This paper presents a model based on multi criteria decision analysis to overcome the problem of aggregate planning. This decision model takes into account performance objectives obtained in the manufacturing strategy planning process. To do so, the decision maker chooses the most appropriate combination of resources to meet foreseen demand, in accordance with trade-offs amongst the performance objectives. Therefore the resulting aggregate plan refl ects the competitive factors of the business. That is, the proposed decision model allows the implementation of the manufacturing strategy by the production function.